Role of Post-translational Modifications in Influenza A Virus Life Cycle and Host Innate Immune Response - Hu, Jiao; Zhang, Lei; Liu, Xiufan (Frontiers in Microbiology, 2020)
Throughout various stages of its life cycle, influenza A virus relies heavily on host cellular machinery, including the post-translational modifications (PTMs) system. During infection, influenza virus interacts extensively with the cellular PTMs system to aid in its successful infection and dissemination. The complex interplay between viruses and the PTMs system induces global changes in PTMs of the host proteome as well as modifications of specific host or viral proteins. The most common PTMs include phosphorylation, ubiquitination, SUMOylation, acetylation, methylation, NEDDylation, and glycosylation. Many PTMs directly support influenza virus infection, whereas others contribute to modulating antiviral responses. In this review, we describe current knowledge regarding the role of PTMs in different stages of the influenza virus replication cycle. We also discuss the concerted role of PTMs in antagonizing host antiviral responses, with an emphasis on their impact on viral pathogenicity and host range.